ANALISIS PENGGUNAAN DUOLINGO SEBAGAI MEDIA PEMBELAJARAN MAHARAH ISTIMA' PADA ABAD 21 - Taufiqurrahman Hidayatullah; Mad Ali; Shofa Musthofa Khalid (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
In the context of Arabic language learning, the role of media is very important to achieve learning success, especially in the development of listening skills. In the 21st century learning era, the emphasis on literacy, practical knowledge, skills, and attitudes is integrated with the understanding and utilization of technology. Duolingo application, as a representation of technology, has a very important role in the learning process, especially in language learning. This study aims to analyze the use of Duolingo as a learning medium and also analyze Duolingo's Lingual Audio for istima learning. The research method used in this study is a qualitative approach with descriptive analysis. The collection of information in the framework of this research involves interview techniques and the interviews used are semi-structured interviews. The research participants consisted of active users of Duolingo application who focus on learning maharah istima' in Arabic language learning. The results showed that the users appreciated the interactive and engaging design offered in the